A novel approach to formulate high flux multifunctional ultrafiltration membranes from photocatalytic titania composite precursors on multi-channel tubular substrates. Issue 63 (21st June 2016) - Manjumol, K. A.; Sankar, S.; Nair, Balagopal N.; Midhun, M.; Mohamed, Peer A.; Warrier, K. G. K.
Abstract : Anatase rich titanium dioxide ultrafiltration membranes with high filtration rates have been successfully developed on multi-channel tubular alumina substrates via aqueous sol–gel method from titania–alumina composite precursors. Abstract : Anatase rich titanium dioxide ultrafiltration membranes with high filtration rates have been successfully developed on multi-channel tubular alumina substrates via aqueous sol–gel method from titania–alumina composite precursors containing 30 wt% alumina. The composite membrane material exhibited anatase phase stability above 800 °C and retained a BET surface area of 64 m 2 g −1 even after calcination at 700 °C. Supported membranes on multi-channel substrates with an active layer thickness of 4 μm gave a water flux value of 215 L m −2 h −1 coupled with 80% rejection of Bovine Serum Albumin (BSA) with molecular weight 66 kD at 2 bar pressure. This is much higher compared to a flux of 27 L m −2 h −1 obtained for a single component titania membrane layer. The composite membrane materials showed excellent photocatalytic activity under UV irradiation such that a solution containing Methylene Blue (MB) dye showed 96% dye degradation within 2 h. Porous disc shaped substrates coated with the active titania composite layer showed methylene blue degradation of 44% under identical conditions. The present results point towards an excellent pathway for the development of multifunctional ultra-filtration membranes for water purification and also for other separation applications where separation together with photocatalysis will be of great importance.